Islamic Financing Instrument Under Indonesia Positive Law - Supardan Mansyur; Usman Usman; Lalu Sabardi (Unram Law Review, 2018)
Islam governs all aspects of human life. It is not regulate the human relation to Allah only but also between human each other, among other economy like financing comply with shari’ah. The issues are: (1) how is the regulation of financing comply with shari’ah regulated ini positive law in Indonesia; and (2) handicap faced in its application in Indonesia. The purposes of this research are to know: (1) its regulation on positive law, and (2) its handicap in its application Indonesia. Its results are: (1) Islamic financing in Indonesia is regulated in various rules and regulation and their implementation strengthening its existing in positive law in Indonesia as Act No.7/1992 on Banking (amended by Act No. 10/1998), Act No. 23/ 1998 on Indonesia Bank (amended by Act No. 3/2004), and Act No. 21/ 2008 on Islamic banking, particular to Shari’ah Capital Market its regulation is regulated by OJK Decision and DSN-MUI Fatwas; (2) murabahah based financing) dominating all financing of Indonesian banking industry is considered as the cause of Islamic Banking avoided to use Mudharabah and Musharakah is their higher risk. Related to these difficulties is recommended to be: (1) expected to Government and DPR to enact the statute on Islamic on Islamic Capital Market putting the Islamic Capital Market equal to the Conventional Capital Markets (2) The role of Government and the other institutions to cope handicap faced as highlight the capacity enhancement of Islamic financing institutions, regulations, and development of infrastructures supporting the Islamic financing application, are absolutely needed.